The health-performance framework of presenteeism: A proof-of-concept study - Biron, Caroline; Karanika-Murray, Maria; Ivers, Hans (Frontiers in Psychology, 2022)
There is emerging research that considers presenteeism as a neutral behavior that has both positive and negative predictors and outcomes for individuals and organizations. This neutral perspective diverges from the traditional negative view of presenteeism and is aligned with the Health-Performance Framework of Presenteeism (HFPF, Karanika-Murray and Biron, 2020) in which presenteeism is considered to be an adaptive behavior that aims to balance health limitations and performance demands. This proof-of-concept study aims to investigate the existence of different profiles of presentees based on their common health problems (mental and physical) and performance, and differences in attendance and job stressors among these subgroups. Latent profile analysis with 159 clerical employees and managers from the UK private sector supported the HPFP and revealed four profiles: those reporting a good health and high performance were labelled functional presentees (who represented 19% of the sample), those with poor health and low performance were the dysfunctional presentees (14%), those with relatively high performance but poor health were labelled overachieving presentees (22%), and those with average scores on both dimensions were the average Joe/Jane presentees (45%; a new profile based on this sample). There was no profile in the present sample that corresponded to therapeutic presenteeism, characterized by low performance but relatively good health. Although average Joe/Jane presentees were comparable to functional presentees in exposure to most job stressors, they reported poorer pay and benefits, and more health problems than the latter. Average Joe/Jane presentees reported the lowest number of days of presenteeism. No difference was found in absenteeism across profiles, highlighting difficulties in measuring presenteeism using a count-measure, since three profiles presented a similar number of days of presenteeism yet contrasted health-performance configurations. Dysfunctional presentees were systematically more exposed to job stressors compared to functional presentees. The results support the HPFP proposition for different subgroups of presentees who are influenced by their work environment. The study takes a person-centered approach, disentangle presenteeism from the total count of presenteeism days, offering implications for management and intervention practice. Presenteeism can have a bright side and be functional in certain contexts when the appropriate resources are available.